The nurse in labor: preventing obstetric violence - Silva, Ivanise Vieira (2024)
Around the world, many women are victims of obstetric violence during the labor process, in hospitals there are various forms of violence and damage caused by the healthcare team during care Objective: discuss the importance of nursing care in coping and prevention of obstetric violence throughout the women's care network from prenatal to postpartum and newborn care. Methodology: The methodology used in this study is an integrative review of the literature with a descriptive approach, with content analysis as its primary characteristic, which synthesized and grouped the results obtained in important research on the topic outlined in previous articles. Result: 10 articles relevant to the chosen theme were synthesized. Conclusion: The importance of this study was guided by the magnitude of the topic for the nursing area, with an emphasis on professionals working in monitoring parturient women from the beginning of prenatal care to delivery and care for newborns.